Effects of the COVID-19 pandemic and previous pandemics, epidemics and economic crises on mental health: systematic review. Issue 6 (10th November 2022) - Asper, Michaela; Osika, Walter; Dalman, Christina; Pöllänen, Elin; Simonsson, Otto; Flodin, Pär; Sidorchuk, Anna; Marchetti, Laura; Awil, Fatima; Castro, Rosa; Niemi, Maria E.
Abstract : Background: A rise in mental illness is expected to follow the COVID-19 pandemic, which has also been projected to lead to a deep global economic recession, further adding to risk factors. Aims: The aim of this review was to assess the impact of the COVID-19 pandemic and previous pandemics, epidemics and economic crises on mental health. Method: Searches were conducted in PubMed, Web of Science, PsycINFO and Sociological Abstracts. We included studies of all populations exposed to the COVID-19 pandemic, and other similar pandemics/epidemics and economic crises, compared with non-exposed time periods or regions. The outcome was mental health. Results: The 174 included studies assessed mental health impacts of the COVID-19 pandemic (87 studies), 2008 economic crisis (84 studies) and severe acute respiratory syndrome (SARS) epidemic (three studies). Outcomes were divided into affective disorders, suicides, mental healthcare utilisation and other mental health. COVID-19 pandemic studies were of lesser quality than those for the economic crisis or SARS epidemic. Most studies for all exposures showed increases in affective disorders and other mental health problems. For economic crisis exposure, increases in mental healthcare utilisation and suicides were also found, but these findings were mixed for COVID-19 pandemic exposure. This is probably because of quarantine measures affecting help-seeking and shorter follow-ups of studies of COVID-19 pandemic exposure. Conclusions: Our findings highlight the importance of available, accessible and sustainable mental health services. Also, socioeconomically disadvantaged populations should be particular targets of policy interventions during the COVID-19 pandemic.